The Relationship between Information Literacy and Playing Skills in Bridge Athletes at Padjadjaran University - Yasmine Kusumawardhani; Edwin Rizal; Asep Saeful Rohman (Jurnal Pustaka Ilmiah, 2025)
This study analyzes the relationship between information literacy and playing skills in bridge athletes at Padjadjaran University. The formulation of the problem in this study is whether there is a relationship between the eight components of the empowering eight information literacy model, namely identification, exploration, selection, organization, creation, presentation, assessment, and application, with bridge playing skills in Padjadjaran University Bridge Athletes. This study uses a quantitative approach with a survey method, where questionnaires are distributed to a research sample of 45 bridge athletes. The study employs a saturated or census sampling technique, which involves including all population members as respondents. The data analysis technique used is the Spearman Rank correlation test to measure the relationship between information literacy and bridge playing skills. The results of the study showed that there was a significant relationship between information literacy and bridge playing skills. The information application subvariable has the strongest influence on bridge playing skills. This finding confirms that bridge athletes with better levels of information literacy have a higher ability to understand strategies and make more appropriate decisions during the match. The conclusion of this study emphasizes the importance of developing information literacy skills in coaching bridge athletes, so that they can be more effective in processing and applying the information obtained. This study suggests the need to strengthen information literacy so that bridge athletes are accustomed to managing information effectively and making it part of the thinking process and decision-making while playing.